EFFECTS OF INDIVIDUAL CHARACTERISTICS AND ORGANIZATIONAL CONTEXT ON SUPERIORS' USE OF CONFLICT STYLES AND SUBORDINATES' SATISFACTION WITH SUPERVISION - Lee Kim Lian; Low Guan Tui (Asian Academy of Management Journal, 2008)
Data from 139 respondents from major industries showed that subordinates were more satisfied with their superiors' supervision through the exercise of integrating, compromising and obliging styles. On the contrary, subordinates who perceived their superiors as primarily using dominating and avoiding styles viewed them as incompetent in supervision and thus lowering their level of satisfaction with supervision. Among the conflict handling styles, integrating was most correlated with organic structure. The organic structure was found to be positively correlated with subordinates' satisfaction. These results implied that organic structure can be a potent force in maintaining organizational stability. The exercise of dominating style was found to be only marginally correlated with superior's age. Superior rank in lower hierarchy level was found to have a negative impact, albeit marginally on the exercise of dominating style. The present results also seemed to suggest that subordinates tend to be less satisfied with superiors with wider span of control.